(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Nefedov I.V. Keywords: concept, love, decadence, individualism, rock-poetry, mystification of reality. The article is devoted to the linguo-cultural emotional concept ‘love’, which represents a complex mental formation. The author makes an attempt to analyze the concept representation in V. and G. Samoilovs’ lyrics. The language analysis of 120 songs has made it possible to conclude the specificity of the concept ‘love’. It is deprived of light, romantic halo. The love in the Samoilovs’ poetry is only a passion, bordering on mystics and striving for something outrageous, love is not a creative, but destructive element.